Human response to controlled levels of combinations of sulfur dioxide and inert dust. - Andersen, Ingelise; Mølhave, Lars; Proctor, Donald F. (Scandinavian Journal of Work, Environment & Health, 1981)
Under controlled conditions in an environmental chamber 16 healthy young volunteers were exposed to combinations of sulfur dioxide (SO2) (2.6 or 13 mg/m3) and inert plastic dust (2 or 10 mg/m3) or of SO2 (13 mg/m3) and dust (10 mg/m3) coated with vanadium. During periods of clean air and during exposures of 5-h duration nasal mucus flow rate, nasal airflow resistance, forced vital capacity, and subjective discomfort were measured. Reductions in nasal mucus flow rate, forced expiratory flow (FEF25-75%), and discomfort were related principally to the SO2 concentration. The combined effects of SO2 and dust were, at the most, additive, and there was no indication of potentiation effects. No effect could be attributed to the coating of the dust with vanadium.
Keywords: airway resistance; combination; controlled level; discomfort; environmental chamber; human response; inert dust; mucociliary clearance; nose; particle; rhinomanometry; sulfur dioxide; vanadium; workroom air